Optimization of Clean Water Services by PERUMDA Tirta Bhagasasi - Lutfi, Reza; Akbar, Bahrullah; Sinurat, Marja (International Journal of Science and Society, 2025)
This study analyzes the optimization of clean water services provided by PERUMDA Tirta Bhagasasi in Bekasi Regency, focusing on institutional performance, service quality, and key factors influencing service delivery. Using a qualitative descriptive case study approach, data were collected through interviews, field observations, and document analysis. The findings show that clean water services have not yet reached optimal standards, as indicated by unequal service distribution, inconsistent water quality, fluctuating water pressure, and limited-service continuity in several areas. Structural constraints such as aging infrastructure, high non-revenue water (NRW), declining raw water quality, and insufficient budget allocation significantly hinder service improvement. Managerial issues, including limited coordination, gaps in human resource competence, and inadequate complaint-response mechanisms, further weaken service effectiveness. The study concludes that optimizing service performance requires an integrated strategy involving infrastructure rehabilitation, capacity enhancement, digital innovation, institutional strengthening, sustainable raw water management, and multi-stakeholder collaboration. These efforts are essential to ensure equitable, efficient, and sustainable clean water services for the growing population of Bekasi Regency.